Unexpected disruption of the dimensionality-driven two-photon absorption enhancement within a multipolar polypyridyl ruthenium complex series - Durand, Nicolas; Mhanna, Rana; Savel, Paul; Akdas-Kilic, Huriye; Malval, Jean-Pierre; Soppera, Olivier; Fillaut, Jean-Luc (ROYAL SOC CHEMISTRY, 2020)
The dimensionality-driven two-photon absorption (2PA) enhancement effect is investigated in a series of functionalized bipyridyl Ru-complexes. Our design strategy leads to very high 2PA responses up to similar to 1500 GM. However, we highlight that the 2PA performancevs.dimensionality correlation reaches an unexpected limit stemming from 'anti-cooperative' interchromophoric couplings.
Keywords: EFFICIENCY; D-2D; D-3; Chemistry